A Model of Academic Self-Concept: Perceived Difficulty and Social Comparison Among Academically Accelerated Secondary School Students. (April 2014) - Wilson, Hope E.; Siegle, Del; McCoach, D. Betsy; Little, Catherine A.; Reis, Sally M.
Academic self-concept predicts students' future goals and is affected by a student's relative success compared with his or her peer group. This exploratory study used structural equation modeling to examine the contributions of the perceived level of difficulty of the curriculum, in addition to the contributions of social comparison and achievement in schoolwork, to academic self-concept among students enrolled in advanced coursework. Along with school achievement, perceived difficulty and social comparison also predicted academic self-concept. The final model indicated that students differentiate between learner self-concept, which is how students perceived their ability to understand new ideas or knowledge, and student self-concept, which is how they perceived their abilities to succeed in school-related tasks. Of these two constructs, student self-concept was a better predictor of future goals; however, the overall effect was small.